Foreign Direct Investment Restriction Policy as an Effort to Empower Micro, Small and Medium Enterprises - Zulfikar, Ary (Indonesian Journal of International Law, 2019)
Foreign Direct Investment is one of the important means to increase a country’s economic growth through equitable development. However, countries such as Indonesia, often put restrictions on their foreign investment policies. The purposes of this research are: 1) to explain the restrictive policies which are imposed upon foreign investments in Indonesia and to compare them to those of other countries in Asia; 2) to explain the practical impact of such restrictive policies on foreign investments in Indonesia. The author uses a qualitative-descriptive research method. The research is also conducted through a juridical normative approach. This research shows that: 1) Restrictions on foreign investment is regulated under the Presidential Regulation of the Republic of Indonesia No. 76 of 2007 on Criteria and Requirements for Formulation of Business Fields Closed to Investment and Business Fields Conditionally Open to Investment; 2) In its implementation, Presidential Regulation No. 76 of 2007 has not yet been able to boost sustainable economic growth evenly via the empowerment of MSMEs or domestic investors.